Development of intelligent system for eye-tracking application - Wu, Chenglong (2017)
This report summarized the whole making process of this project. This project was aspired to provide a feasible solution for physically impaired people to interact with computer sufficiently by performing basic tasks like, control a computer cursor, and browsing a webpage via their eye movements. The success of this project will potentially improve the quality of patients’ life. The eye movement tracking system is a program that captures and tracks the human eye motions using a video camera and it would be translated into practical functions like cursor control, web browser interaction. Through experiment and testing, the reliability of the tracking algorithm (CAMShift) will be affected by factors like the position of camera, the lighting of room, and the intensity of LED light that shines on user’s eye. Adjustment has been constantly made to improve reliability of the system. However, there are much more rooms for improvement for this project.